Targeting Lipooligosaccharide (LOS) for a Gonococcal Vaccine - Gulati, Sunita; Shaughnessy, Jutamas; Ram, Sanjay; Rice, Peter A. (Frontiers in Immunology, 2019)
Gonococcal lipooligosaccharides (LOSs) are potential vaccine candidates because they are densely represented on the bacterial surface and are readily accessible as targets of adaptive immunity. Less well understood is whether LOSs evoke protective immune responses. Although gonococcal oligosaccharides (OSs), derived from LOS, are major immune targets, often they vary as a result of phase variation. These features seemingly make LOSs less desirable as vaccine candidates. However, we have identified a gonococcal LOS-derived OS, called the 2C7 epitope which: i) is a broadly representative antigenic target; ii) serves as a virulence determinant that can be neutralized and iii) is critical for colonization of mice, the latter diminishing the effects of selective pressure. We examined the 2C7 (OS) epitope as a potential gonococcal vaccine candidate. Because of difficulties in purifying OSs from LOSs to maintain structural integrity, we ‘converted’ the 2C7 epitope into a peptide mimic that elicited cross-reactive anti-OS antibodies that possessed complement-dependent bactericidal activity against gonococci. Mice immunized with peptide mimic cleared vaginal colonization more rapidly and reduced gonococcal burdens. Efficacy of active immunization with peptide mimic was paralleled by passive immunization with anti-2C7 monoclonal antibody (Ab). Finally, a human chimeric of 2C7 Ab possessing a complement enhancing mutation in Fc, exceeded efficacy seen with 2C7 Ab. Furthermore, the chimeric functioned in the absence of neutrophils. 2C7 vaccine satisfies criteria that we propose necessary for a gonococcal vaccine: a broadly represented antigenic target that also serves as a virulence determinant and is critical for organism survival in vivo.